(untitled) (Scientific journal of the Fergana State University, 2024)
This article is related to the need of educational technology to develop training-combat qualities in military training cadets based on a competency approach, to ensure the country’s security, strengthen defense capabilities and perform important educational and preventive tasks aimed at protecting citizens, processes are considered. At the same time, the basic tasks of the foundations of the development of educational and combat qualities in military education before the draft, theoretical foundations of innovative methods of improving the system of training specialists in the field of military education for future officers were considered.